2022
DOI: 10.3389/fbioe.2022.877361
|View full text |Cite
|
Sign up to set email alerts
|

The Use of a Replicating Virus Vector For in Planta Generation of Tobacco Mosaic Virus Nanorods Suitable For Metallization

Abstract: The production of designer-length tobacco mosaic virus (TMV) nanorods in plants has been problematic in terms of yields, particularly when modified coat protein subunits are incorporated. To address this, we have investigated the use of a replicating potato virus X-based vector (pEff) to express defined length nanorods containing either wild-type or modified versions of the TMV coat protein. This system has previously been shown to be an efficient method for producing virus-like particles of filamentous plant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Previous work showed that pEff-generated potexvirus and virgavirus VLPs contain RNAs derived from the replication of the vector, reinforcing the idea that an RNA scaffold was important for helical particle formation 37 , 41 . To assess whether this also applies for pEff-produced potyvirid VLPs, we analysed both types of purified SPFMV and SPMMV VLPs.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Previous work showed that pEff-generated potexvirus and virgavirus VLPs contain RNAs derived from the replication of the vector, reinforcing the idea that an RNA scaffold was important for helical particle formation 37 , 41 . To assess whether this also applies for pEff-produced potyvirid VLPs, we analysed both types of purified SPFMV and SPMMV VLPs.…”
Section: Resultsmentioning
confidence: 73%
“…Observations on the distribution of VLP lengths do not fit exactly with the expected sizes of the most abundant RNAs derived from the replicative pEff-vector constructs. In other cases the predicted equivalences were more evident, as found with the tobamovirus TMV 41 and with the potexvirus AltMV 37 , suggesting that for the sweet potato potyvirids the encapsidation of RNAs into VLPs was less strictly regulated. Alternatively, we cannot exclude the possibility that the conditions required for purification might result in partial breakdown of VLPs due to shearing forces.…”
Section: Discussionmentioning
confidence: 96%
“…For the expression of the SAP-M2e recombinant protein in N. bethamiana plants, we used the self-replicating viral vector pEff genome [42] that was used for the production of different recombinant proteins [40,[54][55][56]. The 19S_SAP_Sp_4M2eh protein was successfully expressed at the level of about 100 µg/g of fresh leaf biomass, and the purification yield was about 60 µg per gram.…”
Section: Discussionmentioning
confidence: 99%
“…All these genetic elements are located in the T-DNA region of a binary vector that could be maintained in both E. coli and A. tumefaciens. This pEff vector was previously used for the fast high-level expression of recombinant proteins in plant cells [40,55,56,59].…”
Section: Expression Vectormentioning
confidence: 99%
“…All these genetic elements are located in the T-DNA region of a binary vector that could be maintained in both Escherichia coli and Agrobacterium tumefaciens . This pEff vector was previously used for the fast high-level expression of recombinant proteins in plant cells [ 5 , 24 , 45 , 56 , 77 ].…”
Section: Methodsmentioning
confidence: 99%